Economics Status of Physical Disable People in Birendranagar Municipality - Sapkota, Kiran Kishor (Journal of Gurubaba, 2025)
Disability refers to a physical, mental, cognitive, developmental condition that limits an individual’s ability to perform daily activities independently. It can be congenital or acquired later in life through accidents, diseases, inherited conditions. The Disability Services Act (1993) of Australia defines disability as a permanent or likely permanent impairment that may be intellectual, psychiatric, sensory, physical in nature. In Birendranagar Municipality, the capital of Karnali Province a 2024 survey by Save the Children identified 1,480 persons with disabilities, comprising 54.3% males and 39.3% females. The local government has introduced several economic empowerment programs, including vocational training in areas such as dairy and bakery production, to enhance self-reliance and income opportunities. However, the economic status of people with disabilities remains affected by challenges such as unemployment, low income, limited education, and inadequate government support, highlighting the need for inclusive and sustainable development strategies.